CARDIOVASCULAR DISEASES TREATMENT IN PATIENTS WITH TYPE 2 DIABETES MELLITUS IN CURRENT CLINICAL PRACTICE - I. E. Sapozhnikova; E. I. Tarlovskaya; E. N. Anufrieva (Столичная издательская компания, 2016)
Aim. To evaluate cardiovascular diseases (CVD) treatment in patients with type 2 diabetes mellitus (DM 2) in current clinical practice.Material and methods. A total of 200 patients with DM 2, who consented to take part in the questionnaire, were examined. Questionnaire, clinical and laboratory examinations were conducted.Results. There was a low frequency of CVD recognized and included into clinical diagnosis - angina, history of myocardial infarction and stroke. In majority of the patients decompensated carbohydrate metabolism was observed. This was due to lack of knowledge, inadequate or absent glucose self-monitoring, low frequency of combined glucoselowering therapy. Target level of blood pressure (BP) was registered in 16% of hypertensive patients only. Basic reasons of this were: frequently prescribed mono-therapy, irrational combinations, inadequate dosage and frequent omissions of antihypertensive drugs intake and not appropriate BP self-monitoring. Low frequency of statins therapy and non-targeted cholesterol levels were also revealed in examined patients.Conclusion. Improvement of diagnostic tactics in patients with DM 2 is necessary as well as therapy correction taking into account these patients co-morbidity.